Phase Formation and Ionic Conduction in Potassium-Doped Strontium Metasilicate - Tarique H.; Shahid R.; Singh A.K.; Singh P.; Pandey R.; Singh P. (My University, 2025)
Alkali metal-doped strontium metasilicate has been reported as ion-conducting materials. Here, we report the phase formation in potassium-doped strontium metasilicate (SrSiO3) and also explored the conduction mechanism that is responsible for high ionic conductivity in this system. The phase evolution also explains the conduction behavior. The coexistence of crystalline along with few amount amorphous phases was also found to be responsible for high ionic conduction in the material. The high level of conductivity observed may be due to the oxygen vacancies in these structures generated through the mobile defects. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.